2023
DOI: 10.1039/d3qi01071f
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring photoluminescence and multifunctionalities of lanthanide coordination complexes employing ligand-controlled aggregation states

Jun Wang,
Qianbo Zhang,
Zhiming Chen
et al.

Abstract: Developing lanthanide (III) ion (Ln3+) coordination complexes to mimic sunlight and achieve dynamic anti-counterfeiting is cutting-edge research, but it remains a significant challenge for luminescence color tuning and advanced information...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Ln-based complexes possess fascinating emission features because of their unique 4f electrons, such as long lifetimes and high quantum yields, 52,53 which offer numerous benefits to optical storage, optical communication, and chemical sensing. 54,55 Previous studies showed that the use of π-conjugated ligands and/or close shell ions ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Ln-based complexes possess fascinating emission features because of their unique 4f electrons, such as long lifetimes and high quantum yields, 52,53 which offer numerous benefits to optical storage, optical communication, and chemical sensing. 54,55 Previous studies showed that the use of π-conjugated ligands and/or close shell ions ( e.g.…”
Section: Resultsmentioning
confidence: 99%